2x^2+3x-44=0

Simple and best practice solution for 2x^2+3x-44=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x^2+3x-44=0 equation:


Simplifying
2x2 + 3x + -44 = 0

Reorder the terms:
-44 + 3x + 2x2 = 0

Solving
-44 + 3x + 2x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-11 + -2x)(4 + -1x) = 0

Subproblem 1

Set the factor '(-11 + -2x)' equal to zero and attempt to solve: Simplifying -11 + -2x = 0 Solving -11 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -2x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + -2x = 0 + 11 -2x = 0 + 11 Combine like terms: 0 + 11 = 11 -2x = 11 Divide each side by '-2'. x = -5.5 Simplifying x = -5.5

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {-5.5, 4}

You can always share this solution

See similar equations:

| X^2+10x+22=6 | | x^5+x^4+x^3+x^2+x+3=0 | | x^2+6x-65=0 | | 56x+8x^2=0 | | x^2+6x+8=0 | | x^2+16x=-7 | | 3x^2-24x+1=0 | | 5x^2+6xy+13j^2= | | 2x^2+14x=120 | | 6r^2+11r-10=0 | | 6r^2+10r=0 | | y=4k^2+6k-1 | | 3x^2+16x+64=0 | | 2x^2+8x=90 | | 3x^2+12x=180 | | 4x^2+13x-75=0 | | 4x^2+13-75=0 | | 3x^2+10x-88=0 | | 2v^2-4v+52= | | v^2-4v+16= | | v^2-36= | | 24uxy^5-22u^5y^5= | | 4u^6+6u^5-10u^4= | | 10x^2+12x+18=0 | | 25p^2=4 | | 5x^2=13x+6 | | x^2+10x+25=0 | | X^2+4x+4=0 | | x^2+6x+9=0 | | -4x=2x^2-6 | | -x=2x^2-6 | | -2x=3x^2-1 |

Equations solver categories